Meltblown nonwoven fabric and its composite material
Patent Information
- Application Number
- JP2022502995
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-07-26
- Filing Date
- 2020-07-20
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2040-07-20
Smart Images

Figure 0007652753000014 
Figure 0007652753000015 
Figure 0007652753000001
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE Embodiments of the present disclosure generally relate to meltblown nonwoven fabrics formed from bicomponent fibers and composite structures thereof. [Background technology]
[0002] Nonwovens (NW) are cloth-like materials made from fillers held together via various bonding techniques (e.g., spunbond or meltblown processes). These nonwovens can be used in hygiene and / or medical applications such as disposable absorbent articles, including diapers, wipes, feminine hygiene products, and adult incontinence products. In such applications, spunbond-meltblown-spunbond (SMS) composite structures are becoming increasingly popular.
[0003] Spunbond layers have historically been formed from polypropylene monocomponent fibers due to its mechanical performance. One of the major drawbacks of polypropylene is its lack of flexibility. Flexibility can be addressed by the introduction of polyethylene (PE). Spunbond layers are increasingly being formed from bicomponent fibers with polyethylene resin in the sheath and polypropylene resin in the core. The polyethylene resin provides flexibility and improved tactility, desirable features in hygiene and / or medical applications, while the polypropylene provides strength and fiber spinnability.
[0004] Polypropylene resin is also typically used to form the meltblown layer due to its excellent processing characteristics in the meltblown process. However, in SMS structures, the outer polyethylene sheath of the bicomponent fiber used to form the spunbond nonwoven is bonded to the polypropylene meltblown layer. The melt temperature difference and incompatibility between polyethylene and polypropylene can result in poor bonding between the layers when higher polypropylene melt temperatures are used, as the polyethylene may tend to "run away" from the bond points, and at lower polyethylene melt temperatures, the polypropylene does not melt properly. Thus, the bond strength of the SMS composite structure may be reduced.
[0005] Therefore, alternative resins for use in meltblown nonwovens and SMS composite structures that may exhibit improved bond strength may be desirable. Summary of the Invention
[0006] Disclosed herein is a meltblown nonwoven fabric. The meltblown nonwoven fabric is formed from bicomponent fibers, the bicomponent fibers having a first region and a second region. The first region is formed from a first composition comprising at least 75% by weight of polypropylene, the second region is formed from a second composition comprising at least 75% by weight of an ethylene / alpha-olefin interpolymer having a density of 0.911-0.950 g / cc, a Brookfield viscosity of 50,000 cP or less, and a molecular weight distribution (Mw,cc / Mn,cc) of 1.8-3.5, and the bicomponent fibers have a shear viscosity ratio of the first composition to the second composition of less than 2.0.
[0007] Further disclosed herein is a composite structure. The composite structure includes a meltblown nonwoven fabric. The meltblown nonwoven fabric is formed from bicomponent fibers, the bicomponent fibers having a first region and a second region. The first region is formed from a first composition comprising at least 75% by weight of polypropylene, and the second region is formed from a second composition comprising at least 75% by weight of an ethylene / alpha-olefin interpolymer having a density of 0.911-0.950 g / cc, a Brookfield viscosity of 50,000 cP or less, and a molecular weight distribution (Mw,cc / Mn,cc) of 1.8-3.5, and the bicomponent fibers have a shear viscosity ratio of the first composition to the second composition of less than 2.0.
[0008] In one or more embodiments herein, the ethylene / alpha-olefin interpolymer has a M z,cc / M n,ccIn one or more embodiments herein, the ethylene / alpha-olefin interpolymer has less than 2.5% of a 10 olefin copolymer, based on the total weight of the interpolymer, as determined by conventional gel permeation chromatography. 5 In one or more embodiments herein, the ethylene / alpha-olefin interpolymers have a comonomer distribution breadth index of greater than 50%, or alternatively from 50% to 98%, or alternatively from 50% to 85%.
[0009] In one or more embodiments herein, the bicomponent fiber has a core-sheath structure. In one or more embodiments herein, a first region of the bicomponent fiber is the core and a second region of the bicomponent fiber is the sheath. In one or more embodiments herein, the meltblown nonwoven fabric has a fiber density of 500 l / m at 20 gsm. 2 It exhibits breathability of less than 1 / second.
[0010] In one or more embodiments herein, the composite structure further comprises one or more spunbond nonwovens. In one or more embodiments herein, the composite structure further comprises one or more spunbond nonwovens. a M b S c The nonwoven fabric has the structure: S is a spunbond nonwoven, M is a meltblown nonwoven fabric as described herein, and a, b, and c are the number of layers and are independent integers ranging from 1 to 5. In one or more embodiments herein, the spunbond nonwoven fabric is formed from bicomponent fibers having a sheath-core structure, the sheath comprising polyethylene and the core comprising polypropylene. In one or more embodiments herein, the spunbond nonwoven fabric is formed from monocomponent fibers, the monocomponent fibers comprising polyethylene.
[0011] Additional features and advantages of the embodiments will be set forth in the detailed description which follows, and will be readily apparent in part to those skilled in the art from the description, or will be learned by practicing the embodiments described herein, including the detailed description which follows, the claims, and the accompanying drawings.
[0012] It should be understood that both the foregoing and the following description are intended to describe the various embodiments and provide an overview or framework for understanding the nature and features of the claimed subject matter. The accompanying drawings are included to provide a further understanding of the various embodiments, and are incorporated in and constitute a part of this specification. The drawings illustrate various embodiments described herein and, together with the description, serve to explain the principles and operation of the claimed subject matter. [Brief description of the drawings]
[0013] [Figure 1] 1 is a graph showing a chromatogram plot of detector signal (V) versus retention volume (ml) and the setting of appropriate baseline and integration limits for samples exhibiting clear, distinct antioxidant peaks. [Diagram 2] 1 is a graph showing a chromatogram plot of detector signal (V) versus retention volume (ml) and the appropriate baseline and integration limits set for samples showing continuity to a polyethylene equivalent molecular weight of 100. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Reference will now be made in detail to embodiments of the meltblown nonwoven fabric. The meltblown nonwoven fabric may be used in hygienic absorbent articles, such as diapers, wipes, feminine hygiene products, adult incontinence products, etc. However, it should be noted that this is merely an exemplary implementation of the embodiments disclosed herein. The embodiments are also applicable to other technologies that are susceptible to similar problems as those described above. For example, meltblown nonwoven fabrics that can be used to produce face masks, surgical gowns, isolation gowns, surgical drapes and covers, surgical caps, tissues, bandages, and wound dressings are clearly within the scope of the present embodiments.
[0015] A meltblown nonwoven fabric is formed from one or more bicomponent fibers having a first region and a second region. The first region is formed from a first composition comprising at least 75% by weight polypropylene. All individual values and subranges of at least 75% by weight polypropylene are included and disclosed herein. For example, in some embodiments, the first composition comprises at least 80% by weight, at least 85% by weight, at least 90% by weight, at least 92% by weight, at least 95% by weight, at least 97% by weight, at least 99% by weight, or 100% by weight polypropylene. As used herein, "polypropylene" refers to a polymer comprising units derived from more than 50% by weight propylene monomer. This includes homopolymer polypropylene, random copolymer polypropylene, impact copolymer polypropylene, and propylene-based plastomers and elastomers. These polypropylene materials are generally known to those skilled in the art.
[0016] The first composition may also include up to 25% by weight of additional components such as one or more other polymers and / or one or more additives. Such additives may include, but are not limited to, antistatic agents, color enhancers, dyes, lubricants, fillers, pigments, primary antioxidants, secondary antioxidants, processing aids, UV stabilizers, antiblocking agents, slip agents, tackifiers, flame retardants, antibacterial agents, odor reducing agents, antifungal agents, and combinations thereof. In some embodiments, the first composition may include up to 25% by weight of propylene-based plastomers or propylene-based elastomers (such as Versify and Vistamaxx), low modulus or / and low molecular weight polypropylenes (such as L-Modu from Idemitsu), random copolypropylenes, or propylene-based olefin block copolymers (such as Intune).
[0017] The second region is formed from a second composition comprising at least 75% by weight of ethylene / alpha-olefin interpolymer.All individual values and subranges of at least 75% by weight of ethylene / alpha-olefin interpolymer are included and disclosed herein.For example, in some embodiments, the second composition comprises at least 80% by weight, at least 85% by weight, at least 90% by weight, at least 92% by weight, at least 95% by weight, at least 97% by weight, at least 99% by weight, or 100% by weight of ethylene / alpha-olefin interpolymer.
[0018] The second composition may also include up to 25% by weight of additional components such as one or more other polymers and / or one or more additives. Such additives may include, but are not limited to, antistatic agents, color enhancers, dyes, lubricants, fillers, pigments, primary antioxidants, secondary antioxidants, processing aids, UV stabilizers, antiblocking agents, slip agents, tackifiers, flame retardants, antimicrobial agents, odor reducing agents, antifungal agents, and combinations thereof. In some embodiments, the second composition may include up to 25% by weight of an ethylene-based elastomer (such as Engage or Affinity), an olefin block copolymer (such as Infuse), a propylene-based olefin block copolymer (such as Intune), a liner low density polyethylene having a density of 0.9 to 0.970 g / cc.
[0019] Ethylene / Alpha Olefin Interpolymer "Interpolymer" refers to a polymer prepared by the polymerization of at least two different types of monomers. The general term "interpolymer" includes the terms "copolymer" (usually used to refer to a polymer prepared from two different monomers) and "terpolymer" (usually used to refer to a polymer prepared from three different types of monomers). It also encompasses polymers made by polymerizing four or more types of monomers.
[0020] Ethylene / alpha-olefin interpolymer generally refers to a polymer comprising ethylene and an alpha-olefin having 3 or more carbon atoms. In an embodiment herein, the ethylene / alpha-olefin interpolymer comprises more than 50 wt% of units derived from ethylene (based on the total amount of polymerizable monomers) and less than 30 wt% of units derived from one or more alpha-olefin comonomers. All individual values and subranges of more than 50 wt% of units derived from ethylene and less than 30 wt% of units derived from one or more alpha-olefin comonomers are included and disclosed herein.For example, in some embodiments, the ethylene / alpha-olefin polymer is (a) 55% or more, e.g., 60% or more, 65% or more, 70% or more, 75% or more, 80% or more, 85% or more, 90% or more, 92% or more, 95% or more, 97% or more, 98% or more, 99% or more, 99.5% or more, greater than 50% to 99%, greater than 50% to 97%, greater than 50% to 94%, greater than 50% to 90%, 70% to 99.5%, 70% to 99%, 70% to 99%, 97%, 70%~94%, 80%~99.5%, 80%~99%, 80%~97%, 80%~94%, 80%~90%, 85%~99.5%, 85%~99%, 85%~97%, 88%~99.9%, 88%~99.7%, 88%~99.5%, 88%~99%, 88%~98%, 88%~97%, 88%~95%, 88%~94%, 90%~99.9%, 90%~99.5%, 90%~99%, 90%~97%, 90%~95% , 93% to 99.9%, 93% to 99.5%, 93% to 99%, or 93% to 97% units derived from ethylene; and (b) less than 30 percent, e.g., less than 25 percent, or less than 20 percent, less than 18%, less than 15%, less than 12%, less than 10%, less than 8%, less than 5%, less than 4%, less than 3%, less than 2%, less than 1%, 0.1 to 20%, 0.1 to 15%, 0.1 to 12%, 0.1 to 10%, 0.1 to 8%, 0.1 and 0.5-5%, 0.1-3%, 0.1-2%, 0.5-12%, 0.5-10%, 0.5-8%, 0.5-5%, 0.5-3%, 0.5-2.5%, 1-10%, 1-8%, 1-5%, 1-3%, 2-10%, 2-8%, 2-5%, 3.5-12%, 3.5-10%, 3.5-8%, 3.5%-7%, or 4-12%, 4-10%, 4-8%, or 4-7% of units derived from one or more alpha-olefin comonomers. Comonomer content may be measured using any suitable technique, such as techniques based on nuclear magnetic resonance ("NMR") spectroscopy, for example, by 13C NMR analysis as described in U.S. Patent No. 7,498,282, which is incorporated herein by reference.
[0021] Suitable alpha-olefin comonomers typically have 20 or fewer carbon atoms. The one or more alpha olefins may be selected from the group consisting of C3-C20 acetylenically unsaturated monomers and C4-C18 diolefins. For example, the alpha olefin comonomers may have 3-10 carbon atoms or 3-8 carbon atoms. Exemplary alpha olefin comonomers include, but are not limited to, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, and 4-methyl-1-pentene. The one or more alpha olefin comonomers may be selected, for example, from the group consisting of propylene, 1-butene, 1-hexene, and 1-octene, or alternatively, from the group consisting of 1-butene, 1-hexene, and 1-octene, or alternatively, from the group consisting of 1-hexene and 1-octene. In some embodiments, the ethylene / alpha olefin interpolymers contain greater than 0% to less than 30% by weight units derived from one or more of 1-octene, 1-hexene, or 1-butene comonomers.
[0022] In embodiments described herein, the ethylene / alpha-olefin interpolymers have a density of 0.911 to 0.950 grams per cubic centimeter (g / cc). All individual values and subranges between 0.911 and 0.950 g / cc are included and disclosed herein. For example, in some embodiments, the polyethylene polymer has a density of 0.911 to 0.945 g / cc, 0.911 to 0.940 g / cc, 0.911 to 0.939 g / cc, or 0.911 to 0.935 g / cc. In other embodiments, the polyethylene polymer has a density of 0.915 to 0.935 g / cc. In further embodiments, the polyethylene polymer has a density of 0.920 to 0.935 g / cc. In yet further embodiments, the polyethylene polymer has a density of 0.925 to 0.935 g / cc. Density may be measured according to ASTM D792.
[0023] In addition to density, the ethylene / alpha-olefin interpolymers have a Brookfield viscosity of 50,000 centipoise (cP) or less. All individual values and subranges of 50,000 cP or less are included and disclosed herein. For example, in some embodiments, the ethylene / alpha-olefin interpolymers have a Brookfield viscosity of 45,000 cP or less, 40,000 cP or less, or 35,000 cP or less. In other embodiments, the ethylene / alpha-olefin interpolymers have a Brookfield viscosity of 5,000 cP to 50,000 cP, 5,000 cP to 45,000 cP, or 5,000 cP to 40,000 cP.
[0024] In addition to density and Brookfield viscosity, the ethylene / alpha-olefin interpolymers have a molecular weight distribution (M w,cc / M n,cc The molecular weight distribution is expressed as the number average molecular weight (M n,cc ) to the weight average molecular weight (M w,cc ) ratio (i.e., M w,cc / M n,cc ) and can be measured by gel permeation chromatography (GPC) techniques. All individual values and subranges from 1.8 to 3.5 are included and disclosed herein. For example, in some embodiments, the ethylene / alpha-olefin interpolymers have a molecular weight distribution (M) of 1.9 to 3.5 or 2.0 to 3.5. w,cc / M n,cc In other embodiments, the ethylene / alpha-olefin interpolymers have a molecular weight distribution (M) of 1.8 to 3.0, 1.9 to 3.0, or 2.0 to 3.0. w,cc / M n,cc In further embodiments, the ethylene / alpha-olefin interpolymer has a molecular weight distribution (M) of 1.8 to 2.8, 1.9 to 2.8, or 2.0 to 2.8. w,cc / M n,cc ).
[0025] In addition to density, Brookfield viscosity, and molecular weight distribution, the ethylene / alpha-olefin interpolymers have a M z,cc / M n,cc M z,cc can be described as the z-average molecular weight. All individual values and subranges less than 4.0 are included and disclosed herein. For example, in some embodiments, the ethylene / alpha-olefin interpolymers have an M of less than 3.5. z,cc / M n,cc In other embodiments, the ethylene / alpha-olefin interpolymer has a M from 2.5 to 4.0, or from 2.5 to 3.5. z,cc / M n,cc has.
[0026] Density, Brookfield viscosity, molecular weight distribution, and M z,cc / M n,cc In addition, the ethylene / alpha-olefin interpolymers contain less than 2.5% of a 10 olefin copolymer, based on the total weight of the interpolymer, as determined by conventional gel permeation chromatography. 5 The weight fraction (w) of molecular weight may be greater than 1.0 g / mole. All individual values and subranges less than 2.5% are included and disclosed herein. For example, in some embodiments, the ethylene / alpha-olefin interpolymers have a weight fraction (w) of 10 g / mole or more, based on the total weight of the interpolymer, as determined by conventional gel permeation chromatography. 5 has a weight fraction (w) of molecular weight greater than 100 g / mol.
[0027] Density, Brookfield viscosity, molecular weight distribution, M z,cc / M n,cc , and 10 5In addition to a weight fraction (w) of molecular weight greater than g / mole, the ethylene / alpha-olefin interpolymers may have a comonomer distribution breadth index (CDBI) of 50% or greater. All individual values and subranges of 50% or greater are included and disclosed herein. For example, in some embodiments, the ethylene / alpha-olefin interpolymers have a CDBI of 55% or greater, 60% or greater, 65% or greater, 70% or greater, or 75% or greater. In other embodiments, the ethylene / alpha-olefin interpolymers have a CDBI in the range of 50%-98%, 50%-97%, 55%-98%, 55%-97%, 60%-98%, 60%-97%, 70%-98%, 70%-97%, 75%-98%, or 75%-97%. In further embodiments, the ethylene / alpha-olefin interpolymers have a CDBI in the range of 50% to 85%, 55% to 85%, 60% to 85%, 60% to 80%, 65% to 80%, or 70% to 80%.
[0028] Density, Brookfield viscosity, molecular weight distribution, M z,cc / M n,cc , 10 5 In addition to the weight fraction (w) of molecular weight greater than g / mole, and the CDBI, the ethylene / alpha-olefin interpolymers may have a maximum DSC temperature crystallization peak Tc of 80°C to 110°C. All individual values and subranges between 80°C and 110°C are included and disclosed herein. For example, in some embodiments, the ethylene / alpha-olefin interpolymers have a Tc of 80°C to 105°C, 85°C to 105°C, or 90°C to 105°C. In other embodiments, the ethylene / alpha-olefin interpolymers have a Tc of 95°C to 105°C. The maximum DSC temperature crystallization peak is determined using a differential scanning calorimetry (DSC) method as outlined below.
[0029] Density, Brookfield viscosity, molecular weight distribution, M z,cc / M n,cc , 10 5In addition to the weight fraction of molecular weight greater than g / mole (w), CDBI, and Tc, the ethylene / alpha-olefin interpolymers may have a ΔTm-Tc, which is the temperature difference between the highest DSC temperature melting peak (Tm) and the highest DSC temperature crystallization peak (Tc), of less than 16°C. All individual values and subranges less than 16°C are included and disclosed herein. For example, in some embodiments, the ethylene / alpha-olefin interpolymers may have a ΔTm-Tc of less than 15°C. In other embodiments, the ethylene / alpha-olefin interpolymers may have a ΔTm-Tc of less than 12°C. The highest DSC temperature melting peak (Tm) is determined using a differential scanning calorimetry (DSC) method as outlined below.
[0030] In embodiments herein, ethylene / alpha-olefin interpolymers may be prepared in a solution polymerization process using one or more conventional reactors, such as loop reactors, isothermal reactors, plug flow reactors, and / or stirred tank reactors in parallel, in series, and / or any combination thereof in continuous or batch mode to produce olefin-based polymers, such as ethylene polymers or propylene polymers. The solution phase polymerization process may occur in one or more fully stirred reactors, such as one or more loop reactors or one or more isothermal reactors, at temperatures ranging from 100 to 300° C., such as 120 to 190° C., and pressures ranging from 300 to 1,000 psig, such as 400 to 750 psig. The residence time in a solution phase polymerization process is typically in the range of 2 to 30 minutes, such as 5 to 20 minutes. Ethylene (monomer), solvent, hydrogen, one or more catalyst systems, and one or more comonomers are continuously fed to the reactor. Exemplary solvents include, but are not limited to, isoparaffin and naphthenic acid. For example, such solvents are commercially available under the name ISOPAR E from ExxonMobil Chemical Co., Houston, Texas, or under the name SBP100 / 140 from Shell Chemicals Europe. The effluent from the polymerization reactor (containing the solvent, monomer, comonomer, hydrogen, catalyst components, and molten polymer) exits the reactor and enters a zone where it is contacted with a killer and, optionally, an acid scavenger (such as calcium stearate and water associated with hydration) to stop the reaction and remove hydrogen chloride. In addition, various additives, such as antioxidants, can be added at this point. The stream then passes through another set of static mixing elements, such as Kenics spiral static mixing elements, to uniformly disperse the catalyst kill and additives. The effluent (containing the solvent, monomer, comonomer, hydrogen, catalyst components, and molten polymer) passes through a heat exchanger to increase the stream temperature in preparation for separation of the polymer from the other lower boiling reaction components. The stream then passes through a pressure drop control valve, which is responsible for maintaining the reactor pressure at a specific target value.The stream then enters a multi-stage separation and devolatilization system where the polymer is stripped from the solvent, hydrogen, and unreacted monomer and comonomer. Impurities are removed from the recycled lower boiling reactants before re-entering the reactor. The separated, devolatilized polymer melt is pumped through a heat exchanger to reduce the stream temperature to a range below 200°C, for example below 170°C, or in the range of 50-110°C, thereby producing a cooled polymer melt. The cooled polymer melt is subsequently pumped through a die specifically designed for underwater pelletization, cut into uniform solid pellets, dried, and transferred to a hopper. After confirmation of the initial polymer properties, the solid polymer pellets are transferred to a storage device. The portion removed in the devolatilization step may be recycled or destroyed. For example, a majority of the solvent is recycled back to the reactor after passing through a purification bed. This recycled solvent, which may still have unreacted comonomer in it, is enriched with fresh comonomer before re-entering the reactor. This recycled solvent may also have some hydrogen and is then enriched with fresh hydrogen.
[0031] In some embodiments, ethylene / alpha-olefin interpolymers can be prepared using the catalyst composition via a liquid phase polymerization process in a loop reactor according to the following procedure: All feedstocks (ethylene and one or more alpha-olefin comonomers, such as hexene or octene) and process solvents (isoparaffinic solvents, e.g., ISOPAR E) are purified with molecular sieves before being introduced into the reaction environment. Hydrogen is supplied as a high purity grade and is not further purified. The reactor monomer feed (ethylene) stream is pressurized to a pressure higher than the reaction pressure, e.g., 750 psig, via a mechanical compressor. The solvent and comonomer (one or more alpha-olefin comonomers, such as hexene or octene) feeds are pressurized to a pressure higher than the reaction pressure, e.g., 750 psig, via a mechanical positive displacement pump. The individual catalyst components can be manually batch diluted with purified solvent (ISOPAR E) to the specified component concentrations and pressurized to a pressure higher than the reaction pressure, e.g., 750 psig. All reaction feed streams can be measured with mass flow meters and independently controlled with a computerized automated valve control system.
[0032] A continuous solution polymerization reactor may consist of a liquid-filled, non-adiabatic, isothermal recirculation loop. Independent control of all fresh solvent, monomer, comonomer, hydrogen, and catalyst component feeds is possible. The combined solvent, monomer, comonomer, and hydrogen feed is temperature controlled anywhere between 5°C and 50°C, typically 40°C, by passing the feed streams through heat exchangers. The fresh comonomer feed to the polymerization reactor is aligned to add the comonomer to the recirculating solvent. All fresh feeds to the polymerization reactor are injected into the reactor at two locations, for example, with approximately equal reactor volume between each injection location. The fresh feeds are typically controlled, for example, with each injector receiving half the mass flow rate of all fresh feeds. The catalyst components are injected into the polymerization reactor, for example, through specially designed injection inlet devices, and are mixed into one mixed procatalyst / cocatalyst feed stream before being injected into the reactor. The procatalyst component feeds are computer controlled to maintain the reactant monomer concentration at a specific target value. The cocatalyst components are fed based on a calculated, specified molar ratio to the procatalyst components. Immediately after each fresh injection point (either feed or catalyst), the feed stream is mixed with the contents of the circulation polymerization reactor using static mixing elements, such as Kenics spiral static mixing elements. The reactor contents are continuously circulated through a heat exchanger, which serves to remove most of the heat of reaction, and with the coolant side temperature, which serves to maintain an isothermal reaction environment at the specified temperature. Circulation around the reactor loop can be provided by a screw pump. The effluent from the polymerization reactor (containing the solvent, monomer, comonomer, hydrogen, catalyst components, and molten polymer) exits the reactor and enters a zone in contact with a kill agent and optionally an acid scavenger (e.g., calcium stearate, and water associated with hydration) to stop the reaction and remove hydrogen chloride. Various additives, such as antioxidants, can also be added at this point. The stream then passes through another set of static mixing elements, such as Kenics spiral static mixing elements, to uniformly distribute the catalyst kill and additives.The effluent (containing solvent, monomer, comonomer, hydrogen, catalyst components, and molten polymer) passes through a heat exchanger to increase the stream temperature in preparation for separation of the polymer from other lower boiling reaction components. The stream then passes through a pressure drop control valve, which is responsible for maintaining the reactor pressure at a specific target value. The stream then enters a two-stage separation devolatilization system, where the polymer is stripped from the solvent, hydrogen, and unreacted monomer and comonomer. Impurities are removed from the recycled low boiling reaction components before re-entering the reactor. The separated, devolatilized polymer melt is pumped through a heat exchanger to reduce the stream temperature to a temperature in the range below 200°C, e.g., below 170°C, or in the range of 50-110°C, thereby producing a cooled polymer melt. The cooled polymer melt is subsequently pumped through a die specifically designed for underwater pelletization, cut into uniform solid pellets, dried, and transferred to a hopper. After confirmation of the initial polymer properties, the solid polymer pellets are transferred to a storage device. The portion removed in the devolatilization step may be recycled or destroyed. For example, most of the solvent is recycled back to the reactor after passing through a purification bed. This recycled solvent may still have unreacted comonomer in it and is enriched with fresh comonomer before re-entering the reactor. This recycled solvent may still have some hydrogen and is then enriched with fresh hydrogen.
[0033] In another embodiment, ethylene / alpha-olefin interpolymers may be prepared via a liquid phase polymerization process in two adiabatic stirred tank reactors connected in series using one or more catalyst systems suitable for the polymerization of ethylene and one or more alpha-olefin comonomers according to the following procedure: Ethylene monomer and one or more alpha-olefin comonomers, and hydrogen are combined with a solvent, e.g., an isoparaffinic solvent such as ISOPAR E. Impurities such as water, carbon dioxide, sulfur compounds, etc. are removed from the feed stream, and the feed stream is cooled to a temperature in the range of 5°C to 60°C, e.g., about 13°C, before entering the reactors. The majority of the reaction, about 85 to 90 percent, may occur in the first adiabatic stirred tank reactor. Mixing may be accomplished by circulating the polymer / procatalyst / cocatalyst / solvent / ethylene / one or more alpha-olefin comonomers / hydrogen solution through one or more agitators equipped with mixing blades. The feed (ethylene / one or more alpha-olefin comonomers / solvent / hydrogen) may enter the reactor, for example, from the bottom, and the procatalyst / cocatalyst may also enter the reactor, for example, separately from the feed, from the bottom. The first reactor temperature is in the range of 120° C. to 190° C., for example, about 175° C., and the reactor pressure is in the range of 400 psig to 1,000 psig, for example, about 500 psig. The temperature of the second reactor in series with the first reactor is raised to a temperature in the range of 175° C. to 210° C., for example, about 202° C., where about 10 to 15 percent of the remaining reaction occurs, and no additional catalyst or monomer is added. The average reactor residence time is in the range of 2 to 30 minutes, for example, about 8 minutes for an adiabatic stirred tank reactor before the end of the post-reactor with a fluid specially designed for that purpose.
[0034] The effluent from the polymerization reactor (containing the solvent, monomer, comonomer, hydrogen, catalyst components, and molten polymer) exits the reactor and enters a zone where it contacts a killer and optionally an acid scavenger (e.g., calcium stearate, and water associated with hydration) to stop the reaction and remove hydrogen chloride. In addition, various additives, such as antioxidants, can be added at this point. The stream then passes through another set of static mixing elements, such as Kenics spiral static mixing elements, to uniformly disperse the catalyst kill and additives. The effluent (containing the solvent, monomer, comonomer, hydrogen, catalyst components, and molten polymer) passes through a heat exchanger to increase the stream temperature in preparation for separation of the polymer from the other lower boiling reaction components. The stream then passes through a pressure drop control valve that is responsible for maintaining the reactor pressure at a specific target value. The stream then enters a two-stage separation devolatilization system where the polymer is stripped from the solvent, hydrogen, and unreacted monomer and comonomer. Impurities are removed from the recycled lower boiling reactants before re-entering the reactor. The separated, devolatilized polymer melt is pumped through a heat exchanger to reduce the stream temperature to a range below 200°C, for example below 170°C, or in the range of 50-110°C, thereby producing a cooled polymer melt. The cooled polymer melt is subsequently pumped through a die specifically designed for underwater pelletization, cut into uniform solid pellets, dried, and transferred to a hopper. After confirmation of the initial polymer properties, the solid polymer pellets are transferred to a storage device. The portion removed in the devolatilization step may be recycled or destroyed. For example, most of the solvent is recycled back to the reactor after passing through a purification bed. This recycled solvent may still have unreacted comonomer in it and is enriched with fresh comonomer before re-entering the reactor. This recycled solvent may still have some hydrogen and is then enriched with fresh hydrogen.
[0035] Bicomponent Fiber / Meltblown Nonwoven The bicomponent fibers described herein have a shear viscosity ratio of the first composition to the second composition of less than 2.0. (In this specification, this is also referred to as the "complex viscosity ratio.") All individual values and subranges less than 2.0 are included and disclosed herein. For example, in some embodiments, the bicomponent fibers have a shear viscosity ratio of the first composition to the second composition of less than 1.5, less than 1.0, less than 0.95, or less than 0.90. In other embodiments, the bicomponent fibers have a shear viscosity ratio of the first composition to the second composition of 0.5 to 2.0, 0.5 to 1.5, or 0.5 to 1.0. In further embodiments, the bicomponent fibers have a shear viscosity ratio of the first composition to the second composition of 0.75 to 2.0, 0.75 to 1.5, or 0.75 to 1.0.
[0036] In some embodiments herein, the bicomponent fibers have a core-sheath structure. The first region may include the core and the second region may include the sheath. Alternatively, the first region may include the sheath and the second region may include the core.
[0037] Meltblown nonwoven fabrics are formed from bicomponent fibers by extruding the first and second compositions as molten threads or filaments through a plurality of fine, usually circular die capillaries into a converging, high velocity gas stream (e.g., air) that serves to attenuate and reduce the diameter of the threads or filaments. The filaments or threads are then carried by the high velocity gas stream and deposited on a collection surface to form a nonwoven web of randomly distributed meltblown bicomponent fibers, generally having an average diameter smaller than 10 microns. The terms "nonwoven," "nonwoven web," and "nonwoven fabric" are used interchangeably herein. "Nonwoven" refers to a web or fabric that has a structure of individual fibers or threads interleaved randomly, rather than in a identifiable manner as in knitted fabrics.
[0038] Meltblown nonwovens may be used in composite structures. The composite structure may further include one or more spunbond nonwovens. As used herein, "spunbond" refers to fibers formed by extruding a molten thermoplastic polymer composition as filaments through a plurality of fine, usually circular, die capillaries of a spinneret of the diameter of the extruded filaments, which are then rapidly reduced in diameter, after which the filaments are deposited on a collecting surface to form a web or fabric of randomly distributed spunbond fibers, generally having an average diameter of about 7 to about 30 microns. Spunbond fibers may be bicomponent or monocomponent fibers. Monocomponent fibers include polyethylene. Bicomponent fibers may have a sheath-core configuration, with the sheath including polyethylene and the core including polypropylene. Of course, other configurations of bicomponent fibers may be used, such as side-by-side, pie, or "islands in the sea" configurations.
[0039] In some embodiments, the complex comprises S a M b S c configuration, where S is a spunbond nonwoven, M is a meltblown nonwoven as described herein, and a, b, and c are the number of layers and are independent integers ranging from 1 to 5. For example, the composite may have a configuration where "a", "b", and "c" are each independently SMS (where a=1, b=1, and c=1), SMMS (a=1, b=2, and c=1), SSMSS (a=2, b=1, and c=2), SMMMS (a=1, b=3, and c=1), SMMSS (a=1, b=3, and c=2), or other configurations.
[0040] Test Method density Density is measured in accordance with ASTM D-792 and is expressed in grams per cubic centimeter (g / cc).
[0041] Melt Index (I2) / Melt Flow Rate The melt index (I2) is measured according to ASTM 1238 at 190° C. and 2.16 kg and is expressed in grams dissolved / 10 min (g / 10 min). The melt flow rate is measured according to ISO 1133 at 230° C. and 2.16 kg.
[0042] Brookfield Viscosity Brookfield Viscosity is measured using a DV-II Pro Extra Viscometer. The instrument uses Rheocalc V3.3 software, which provides superior control and accuracy of the viscometer. An 8 gram sample is used when using the SC4-31 spindle size. The test temperature is 350°F. An appropriate spindle speed is applied so that the torque is at a level between 40%-70%. Viscosity data is recorded 20 minutes after a stable viscosity reading is obtained.
[0043] Complex Viscosity Dynamic frequency sweep measurements are performed on an ARES-2 rheometer at 210 °C using 2 mm compression molded plaques. Each material is vacuum dried at 80 °C for 2 h, then compression molded at 190 °C and cooled with the aid of a cooling cassette (to avoid the crystallization behavior of the PP material). The applied strain is in the range of 10-20%. The plate diameter is 50 mm. The applied frequency range is 0.1-100 s -1 The plate gap is 1 mm. All measurements are performed under nitrogen to avoid material degradation.
[0044] Conventional GPC Conventional GPC is obtained by a high temperature gel permeation chromatography (GPC) instrument (PolymerChar, Spain). The IR5 detector ("measurement channel") is used as a concentration detector. GPCOne software (PolymerChar, Spain) is used to calculate the z-average (Mz,cc), weight-average (Mw,cc) and number-average (Mn,cc) molecular weights of the polymers and to determine the MWD (=Mw,cc / Mn,cc). The method uses three 10 micron PL Gel Mixed B columns (Agilent Technologies, column dimensions 100 x 7.6 mm) or four 20 micron PL Gel Mixed A columns (Agilent Technologies, column dimensions 100 x 7.6 mm) operating at a system temperature of 150 °C. Samples are prepared at a concentration of 2 mg / mL in 1,2,4-trichlorobenzene solvent containing 200 parts per million of the antioxidant butylated hydroxytoluene (BHT) at 160 °C for 3 h with gentle shaking in an autosampler (PolymerChar, Spain). The flow rate is 1.0 mL / min and the injection size is 200 microliters. The number of plates is calculated using the GPCOne software. A minimum of 22,000 plates are required for the chromatography system.
[0045] The GPC column set is calibrated by running at least 20 narrow molecular weight distribution polystyrene standards. Calibration uses a third order fit to a system with three 10 micron PL Gel Mixed B columns or a fifth order fit to a system with four 20 micron PL Gel Mixed A columns. The molecular weights (MW) of the standards range from 580 g / mol to 8,400,000 g / mol, and the standards are included in six "cocktail" mixtures. There is roughly 10 years of separation between the individual molecular weights in each standard mixture. The standard mixtures are purchased from Agilent Technologies. The polystyrene standards are prepared at 0.025 g in 50 mL of solvent for molecular weights equal to or greater than 1,000,000 g / mol, and at 0.05 g in 50 mL of solvent for molecular weights less than 1,000,000 g / mol. The polystyrene standards are dissolved at 80°C with gentle agitation for 30 minutes. The narrow standards mixtures were run first and in order of decreasing highest molecular weight component to minimize degradation. Polystyrene standard peak molecular weights were converted to polyethylene molecular weights using equation (1) (as explained in Williams and Ward, J. Polym. Sci., Polym. Letters, 6, 621 (1968)).
number
number
[0046] Chromatographic peaks should be set to contain areas that show significant visible deviations from the baseline when the chromatogram is displayed at 20 percent peak height. The baseline should not be integrated to less than 100 polyethylene equivalent molecular weights, and care should be taken in accounting for discrepancies in antioxidants from prepared samples and chromatographic mobile phases. Referring to Figure 1, an appropriate baseline and integration limits set for a sample exhibiting clear, distinct antioxidant peaks is shown.
[0047] The use of a decane flow marker is shown in the IR5 chromatogram (see Figures 1 and 2). The difference in baseline (response) Y values between the start and end of the baseline should not exceed 3 percent of the integrated peak height of the chromatogram. In such cases, chromatographic samples should be treated with appropriate matching of antioxidants in the sample and mobile phase.
[0048] Referring to Figure 2, there is shown a suitable baseline and integration limits set for a sample showing continuity to a polyethylene equivalent molecular weight of 100. The end of the integration limits should not be set below a polyethylene equivalent molecular weight of 100.
[0049] w(10 5 The weight fraction above Mcc,i (g / mol) is calculated according to the MWD curve (wi vs. log Mcc,i) obtained from the GPCOne software according to equation (5).
number
[0050] Triple detector gel permeation chromatography (TDGPC)-light scattering GPC For the GPC technique used herein (light scattering GPC), a triple detector gel permeation chromatography (3D-GPC or TDGPC) system was used. The system consists of a GPC-IR high temperature chromatograph from PolymerChar (Valencia, Spain) equipped with a two-angle laser light scattering (LS) detector type 2040 from Precision Detectors (now Agilent Technologies), an IR5 infrared detector, and four capillary viscometer detectors from PolymerChar. Data collection and data processing are performed using PolymerChar's "Instrument Control" and GPCOne software. The system was also equipped with an online solvent degasser from Agilent Technologies (CA, USA). The GPCOne software is used to calculate the plate number. A minimum of 22,000 plates are required for the chromatography system.
[0051] The eluent from the GPC column set flows through each detector arranged in series in the following order: IR5 detector, LS detector, then viscometer detector. A systematic approach for the determination of multidetector offsets is performed by optimizing the log(MW and intrinsic viscosity) of the triple detectors resulting from the use of broad polyethylene standards, as outlined below, in a manner consistent with that published by Balke, Mourey et al. (Mourey and Balke, Chromatography Polym., Chapter 12, (1992)) (Balke, Thitiratsakul, Lew, Cheung, Mourey, Chromatography Polym., Chapter 13, (1992)).
[0052] Four 20 micron mixed pore size packings ("Mixed A", Agilent Technologies) are used for the separation. The PolymerChar Autosampler oven compartment is operated at 160°C for 3 hours with slow shaking and the column compartment is operated at 150°C. Samples are prepared at a concentration of "2 milligrams per milliliter". The chromatographic and sample preparation solvent is 1,2,4-trichlorobenzene (TCB) containing "200 ppm of 2,6-di-tert-butyl-4 methylphenol (BHT)". The solvent is sparged with nitrogen. The injection volume is 200 microliters. The flow rate through the GPC is set at 1 ml / min.
[0053] For LS GPC, a Precision Detector PDI2040 detector type 2040 15° angle is used. Molecular weight data is obtained in a manner consistent with that published by Zimm (Zimm, BH, J. Chem. Phys., 16, 1099 (1948)) and Kratochvil (Kratochvil, P., Classical Light Scattering from Polymer Solutions, Elsevier, Oxford, NY (1987)), which are incorporated herein by reference. The overall injection concentration used in determining the molecular weight is obtained from the mass detector (IR5) area and mass detector constant derived from a suitable linear polyethylene homopolymer or one of the polyethylene standards of known weight average molecular weight. The calculated molecular weight is obtained using the light scattering constant derived from one or more of the polyethylene standards described below, and a refractive index concentration coefficient, dn / dc, of 0.104. Generally, the mass detector response and light scattering constant should be determined from a linear standard with a molecular weight greater than about 50,000 g / mol. Calibration of the viscometer can be accomplished using methods described by the manufacturer, or alternatively, by using the published values of suitable linear standards, such as Standard Reference Material (SRM) 1475a (available from the National Institute of Standards and Technology (NIST)). The chromatographic concentration is assumed to be low enough to preclude addressing the second viral coefficient effect (concentration effect on molecular weight).
[0054] According to 3D-GPC, the absolute weight average molecular weight (M w,abs " ) and absolute z-average molecular weight (" M z,abs ") is M w,abs is determined using the following equations (6) and (7), which are obtained using the "peak area" method (after detector calibration relating area to mass and mass-molecular weight product) for greater accuracy and precision. "LS.Area" and "Concentration.Area" are generated by the chromatograph / detector combination.
number
[0055] The weight average molecular weight by light scattering (LS) using equation (6) is commonly referred to as the "absolute weight average molecular weight" or "M w,abs " M from equations (2, 3, and 4) n,cc , M w,cc , and M. z,cc is calculated using a conventional GPC molecular weight calibration curve ("conventional calibration"), w,cc is often referred to as "polymer chain backbone molecular weight", "conventional weight average molecular weight", and "M w,cc "It is called "
[0056] Differential Scanning Calorimetry (DSC) Differential scanning calorimetry (DSC) was used to measure the melting and crystallization behavior of polymers over a wide range of temperatures. For example, a TA Instruments Q1000 DSC equipped with an RCS (refrigerated cooling system) and an autosampler was used to perform this analysis. A nitrogen purge gas flow rate of 50 ml / min was used during testing. Each sample was melt pressed into a thin film at approximately 175°C, and then the molten sample was air-cooled to room temperature (approximately 25°C). Film samples were formed by pressing 0.1-0.2 grams of sample at 175°C and 1,500 psi for 30 seconds to form a 0.1-0.2 mil thick film. 3-10 mg, 6 mm diameter specimens were pulled from the cooled polymer, weighed, placed in light aluminum pans (approximately 50 mg) and crimped shut. Analysis was then performed to determine its thermal properties.
[0057] The thermal behavior of the sample was determined by ramping the temperature of the sample up and down to generate a heat flow vs. temperature profile. To remove its thermal history, the sample was first rapidly heated to 180°C and held isothermally for 5 minutes. The sample was then cooled to -40°C at a cooling rate of 10°C / min and held isothermally at -40°C for 5 minutes. The sample was then heated to 150°C at a heating rate of 10°C / min (this is the "second heat" gradient). A cooling curve and a second heating curve were recorded. The cooling curve was analyzed by setting a baseline end point from the onset of crystallization to -20°C. The heating curve was analyzed by setting a baseline end point from -20°C to the end of melting. The values determined were the maximum peak melting temperature (T m ), maximum peak crystallization temperature (T c ), heat of fusion (H f ) (Joules / gram), and crystallinity % = ((H f The calculated crystallinity percentage for the polyethylene sample was calculated using the heat of fusion (H f ) and maximum peak melting temperature were reported from the second heat curve. The maximum peak crystallization temperature was determined from the cooling curve.
[0058] Crystallization Elution Fractionation (CEF) method Comonomer distribution analysis, also commonly referred to as short chain branching distribution (SCBD), is measured using a crystallization elution fractionation (CEF) (PolymerChar, Spain) (Monrabal et al., Macromol. Symp. 257, 71-79 (2007), incorporated by reference) equipped with an IR-4 detector (PolymerChar, Spain) and a two-angle light scattering detector model 2040 (Precision Detectors, now Agilent Technologies). An IR-4 or IR-5 detector was used. A 50 x 4.6 mm 10 or 20 micron guard column (PolymerLab, now Agilent Technologies) was installed just before the IR-4 or IR-5 detector was placed in the detector oven. Ortho-dichlorobenzene (ODCB, 99% anhydrous grade) and 2,5-di-tert-butyl-4-methylphenol ("BHT", catalog number B1378-500G, batch number 098K0686) were obtained from Sigma-Aldrich. The ODCB was distilled before use. Silica gel 40 (particle size 0.2-0.5 mm, catalog number 10181-3) was also obtained from EMD Chemicals. The silica gel was dried in a vacuum oven at 160°C for approximately 2 hours before use. 800 milligrams of BHT and 5 grams of silica gel were added to 2 liters of ODCB. The ODCB can also be dried by passing it through a column(s) packed with silica gel. For a CEF apparatus equipped with an autosampler with N2 purge capability, silica gel 40 is packed into two 300 x 7.5 mm GPC sized stainless steel columns, and the silica gel 40 columns are attached to the inlet of the pump of the CEF apparatus to dry the ODCB, and no BHT is added to the mobile phase. This "ODCB containing BHT and silica gel" or ODCB dried with silica gel 40 is referred to herein as "ODCB". This ODCB is sparged with dry nitrogen (N2) for 1 hour before use. Dry nitrogen is obtained by passing nitrogen through CaCO3 and 5 Å molecular sieves at less than 90 psig. The resulting nitrogen should have a dew point of about -73°C.Sample preparation is performed with an autosampler at 4 mg / ml (unless otherwise specified) with shaking at 160° C. for 2 hours. Injection volume is 300 μl. The temperature profile for CEF is crystallization from 110° C. to 30° C. at 3° C. / min, thermal equilibration at 30° C. for 5 min (with soluble fraction elution time set at 2 min), elution from 30° C. to 140° C. at 3° C. / min. The flow rate during crystallization is 0.052 ml / min. The flow rate during cooling step is 0.052 mL / min. The flow rate during elution is 0.50 ml / min. Data is collected at 1 data point / sec. The CEF column is packed with glass beads of 125 μm ± 6% (MO-SCI Specialty Products) using 1 / 8 inch stainless steel tubing according to U.S. Pat. No. 8,372,931, which is incorporated herein by reference. The column outer diameter (OD) is 1 / 8 inch. The important parameters required to reproduce this method include the column inner diameter (ID) and column length (L). The selection of ID and L should be such that the liquid internal volume is 2.1-2.3 mL when packed with 125 μm diameter glass beads. If L is 152 cm, ID should be 0.206 cm and wall thickness should be 0.056 cm. Different values for L and ID can be used as long as the glass beads have a diameter of 125 μm and the liquid internal volume is 2.1-2.3 mL. Column temperature calibration is performed by using a NIST standard reference material in ODCB, a mixture of linear polyethylene 1475a (1.0 mg / ml) and eicosane (2 mg / ml). CEF temperature calibration consists of four steps: (1) calculating the delay volume, defined as the temperature offset, which is the measured peak elution temperature of eicosane minus 30.00 °C; (2) subtracting the temperature offset of the elution temperature from the CEF raw temperature data.It should be noted that this temperature offset is a function of experimental conditions such as elution temperature, elution flow rate, etc.; (3) creating a linear calibration curve, converting the elution temperature in the range of 30.00 °C to 140.00 °C, such that NIST linear polyethylene 1475a has a peak temperature of 101.0 °C and eicosane has a peak temperature of 30.0 °C; (4) linearly estimating the elution temperature for the soluble fraction measured isothermally at 30 °C by using an elution heating rate of 3 °C / min. The reported elution peak temperatures are obtained such that the observed comonomer content calibration curve matches that previously reported in U.S. Patent No. 8,372,931, which is incorporated herein by reference. CEF data are processed by GPCOne software (PolymerChar, Spain).
[0059] Comonomer Distribution Breadth Index (CDBI) CDBI is defined as the weight percent of polymer molecules having a comonomer content within 50 percent of the median total comonomer content (reported in WO93 / 03093, which is incorporated herein by reference). The CDBI of polyolefins can be conveniently calculated from short chain branching distribution (SCBD) data obtained from techniques known in the art, such as temperature rising elution fractionation ("TREF"), as described, for example, by Wild, et al., Journal of Polymer Science, Poly.Phys. Ed., Vol. 20,441 (1982); LD Cady, "The Role of Comonomer Type and Distribution in LLDPE Product Performance," SPE Regional Technical Conference, Quaker Square Hilton, Akron, OH, 107-119 (Oct. 1-2, 1985), or U.S. Pat. No. 4,798,081 (Hazlitt et al.) and U.S. Pat. No. 5,008,204 (Stehling), all of which are incorporated herein by reference.
[0060] Herein, the CDBI is calculated using the SCBD measured by the CEF according to the following steps: (A) Equation
number
[0061] (B) Median temperature (T 中央値 The cumulative weight fraction over the entire elution temperature range (typically between 20.0 and 120.0 °C) is normalized as 1.00.
[0062] (C) Calibration of comonomer content against elution temperature to obtain median temperature (T 中央値 ) in mole percent (C 中央値 ) and calculate the median of the corresponding total comonomer content in
[0063] (D) A comonomer content calibration curve is created by using a series of reference materials (ethylene-octene copolymers) with known comonomer content, i.e., 11 reference materials with narrow comonomer distribution (monomodal comonomer distribution in CEF from 35.0 to 119.0° C.) and weight average Mw (by conventional GPC) of 35,000 to 115,000 (measured by conventional GPC) with comonomer content ranging from 0.0 mol % to 7.0 mol %, analyzed by CEF at the same experimental conditions specified in the CEF experimental section. The comonomer content of the reference materials is determined using 13C NMR analysis, for example, according to the techniques described in U.S. Pat. No. 5,292,845 (Kawasaki et al.), and by JC Randal in Rev. Macromol. Chem. Phys., C29, 201-317, which are incorporated herein by reference.
[0064] (E) Peak temperature (T p), and the comonomer content is used to calculate the comonomer content calibration, which is calculated from each reference material shown in Formula 4, FIG. 4, where R 2 is the correlation constant.
number
[0065] (F) CDBI, 0.5*C 中央値 ~1.5*C 中央値 The CDBI is calculated as a percentage of the total weight with a comonomer content in the range of 0.94 to 100%. If the density of the polymer is greater than 0.94, the CDBI is therefore defined as 100% (see WO 1993 / 003093(A1) which is incorporated herein by reference).
[0066] Breathable Air permeability is tested in accordance with EDANA WSP 70.1 using an FX 3300 Air Permeability Tester III manufactured by TexTest Instruments, expressed in cubic feet per minute. The test pressure is 200 Pa and the test area is 20 cm 2 It is. EXAMPLES
[0067] material Polymer 1 (Poly.1) is a polypropylene homopolymer (Borflow™ HL512FB) available from Borealis AG (Vienna, Austria) with a melting point of 158° C. (ISO 11357-3) and a melt flow rate (MFR) of 1200 g / 10 min (ISO 1133, 230° C., 2.16 kg). Additional properties of the polymer are shown in the table below.
[0068] Polymer 2 (Poly.2) is an ethylene / alpha-olefin interpolymer available as DNDA 1082 NT7 from The Dow Chemical Company (Midland, Mich.). Additional properties of the polymer are shown in the table below.
[0069] Preparation of the Polymers of the Invention The inventive ethylene / alpha-olefin interpolymers were prepared according to the following process and based on the reaction conditions reported in Tables 1 and 2.
[0070] All raw materials (monomers and comonomers) as well as process solvents (high purity isoparaffinic solvent with narrow boiling range, Isopar-E) are purified with molecular sieves prior to introduction into the reaction environment. Hydrogen is supplied under pressure as a high purity grade and is not further purified. The reactor monomer feed stream is pressurized to above reaction pressure via mechanical compressors. Solvent and comonomer feeds are pressurized to pressures above reaction pressure via pumps. Individual catalyst components are manually batch diluted with purified solvent to specified component concentrations and pressurized to pressures above reaction pressure. All reaction feed streams are metered with mass flow meters and independently controlled by computer automated valve control systems.
[0071] The continuous solution polymerization reactor consists of a liquid-filled, non-adiabatic, isothermal circulating loop reactor similar to a continuous stirred tank reactor (CSTR) with heat removal. Independent control of all fresh solvent, monomer, comonomer, hydrogen, and catalyst component feeds is possible. The total fresh feed streams to the reactor (solvent, monomer, and hydrogen) are temperature controlled by passing the feed streams through heat exchangers. The total fresh feed to the polymerization reactor is injected into the reactor at two locations, with approximately equal reactor volume between each injection location. The fresh feed is controlled with each injector receiving half of the total fresh feed mass flow rate. The catalyst components are injected into the polymerization reactor through specially designed injection stringers. The main catalyst component feeds are computer controlled to maintain the reaction monomer conversion at a specific target value. The cocatalyst components are fed based on a calculated, specified molar ratio to the main catalyst component. Immediately after each reactor feed injection point, the feed streams are mixed with the circulating polymerization reactor contents using static mixing elements. The contents of the reactor are continuously circulated through a heat exchanger, which serves to remove most of the heat of reaction, with the coolant side serving to maintain an isothermal reaction environment at a specific temperature. Circulation around the reactor loop is provided by a pump.
[0072] The final reactor effluent enters a zone where the effluent is deactivated by addition and reaction with a suitable reagent (water). At this same reactor exit location, other additives are added for polymer stabilization. For the samples of the present invention, conditions were selected such that at least a 10-fold molar ratio of (hydrated) water to active catalyst was available to terminate the polymerization in the reactor effluent. This aspect is important to ensure that the polymeric material has a narrow molecular weight distribution and that the composition distribution remains narrow.
[0073] Following catalyst deactivation and additive addition, the reactor effluent enters a devolatilization system where polymer is removed from the non-polymer stream. The isolated polymer melt is processed and pelletized according to the description provided in WO2015 / 191066, pg.6, ll.23-28, pg.8, ll.11-16, and pg.11, ll.3-25, which are incorporated herein by reference. The non-polymer stream passes through various equipment that separates most of the ethylene, which is removed from the system. Most of the solvent and unreacted comonomer are recycled to the reactor after passing through a purification system. Small amounts of solvent and comonomer are purged from the process. [Table 1] [Table 2]
[0074] Each reaction resulted in the production of a polymer solution containing a low molecular weight copolymer with properties as set forth in Table 3. "NM" refers to a value not determined. [Table 3]
[0075] Nonwoven fabric processing conditions Monolithic meltblown nonwoven fabrics of 5 gsm, 20 gsm, and 40 gsm are produced using a 0.5 meter Hills meltblown line at the European Center for Innovative Textiles (CETI) in Tourcoing, France. A single row sheath-core bicomponent Hills die with 0.25 mm hole size and 35 holes / inch is used to create the nonwoven fabrics. The throughput rate per hole is set at 0.2 g / min. The air gap is set at 0.015 inches. Additional process conditions are shown in Table 4. [Table 4] [Table 5] [Table 6] [Table 7]
[0076] Referring to Tables 5-7, the nonwoven fabrics of the present invention show improved breathability since lower breathability is an indicator of better barrier properties over comparative nonwoven fabrics 1-3. The nonwoven fabrics of the present invention consistently provide lower breathability compared to comparative nonwoven fabrics 1-3.
[0077] The dimensions and values disclosed herein should not be understood to be strictly limited to the exact numerical values recited. Instead, unless otherwise specified, each such dimension is intended to mean both the recited value and a functionally equivalent range surrounding that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm."
[0078] All documents cited herein, including any cross-referenced or related patents or applications, if any, and any patent applications or patents to which this application claims priority or benefit, are hereby incorporated by reference in their entirety, unless expressly excluded or otherwise limited. The citation of any document is not an admission that it is prior art with respect to any invention disclosed or claimed herein, or that it alone, or in any combination with any other reference, teaches, suggests, or discloses such invention. Furthermore, to the extent that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this document shall apply.
[0079] While particular embodiments of the present invention have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the invention. Therefore, it is intended in the appended claims to cover all such changes and modifications that are within the scope of this invention. The present application provides, for example, the following inventions. [1] A meltblown nonwoven fabric formed from bicomponent fibers, the bicomponent fiber having a first region and a second region; the first region is formed from a first composition comprising at least 75% by weight polypropylene; the second region is formed from a second composition comprising at least 75 weight percent of an ethylene / alpha-olefin interpolymer having a density of 0.911 to 0.950 g / cc, a Brookfield viscosity of 50,000 cP or less, and a molecular weight distribution (Mw,cc / Mn,cc) of 1.8 to 3.5; The bicomponent fibers have a shear viscosity ratio of the first composition to the second composition of less than 2.0. [2] The meltblown nonwoven fabric of [1] above, wherein the ethylene / alpha-olefin interpolymer has a Mz,cc / Mn,cc of less than 4.0, or alternatively less than 3.5. [3] The meltblown nonwoven fabric according to [1] or [2] above, wherein the ethylene / alpha-olefin interpolymer has a weight fraction (w) of greater than 105 g / mole, based on the total weight of the interpolymer, as determined by conventional gel permeation chromatography, of less than 2.5%, or alternatively less than 1.0%. [4] The meltblown nonwoven fabric according to any one of [1] to [3] above, wherein the ethylene / alpha-olefin interpolymer has a comonomer distribution breadth index of more than 50%, or alternatively from 50% to 98%, or alternatively from 50% to 85%. [5] The meltblown nonwoven fabric according to any one of the above [1] to [4], wherein the bicomponent fibers have a core-sheath structure. [6] The meltblown nonwoven fabric described in [5] above, wherein the first region is a core region and the second region is a sheath region. [7] The meltblown nonwoven fabric has a melt flow rate of 500 l / m at 20 gsm. 2 The meltblown nonwoven fabric according to any one of the above [1] to [6], which exhibits an air permeability of less than 1 / sec. [8] A composite structure comprising the meltblown nonwoven fabric described in [1] to [7] above. [9] The composite structure of [8] above, wherein the composite structure further comprises one or more spunbond nonwoven fabrics.
[10] A composite structure having a SaMbSc configuration, in which S is a spunbond nonwoven fabric, M is a meltblown nonwoven fabric according to the above [1] to [7], and a, b, and c are the number of layers and are independent integers in the range of 1 to 5.
[11] The composite structure of
[10] above, wherein the spunbond nonwoven fabric is formed from bicomponent fibers having a core-sheath structure, the sheath comprising polyethylene and the core comprising polypropylene.
[12] The composite structure of
[10] above, wherein the spunbond nonwoven fabric is formed from a single component fiber, the single component fiber comprising polyethylene.
Claims
1. A meltblown nonwoven fabric formed from bicomponent fibers, the bicomponent fiber has a first region and a second region and has a core-sheath structure, the first region being a core region and the second region being a sheath region; the first region is formed from a first composition comprising at least 75% by weight of polypropylene; the second region is formed from a second composition comprising at least 75 wt.% of an ethylene / alpha-olefin interpolymer having a density of 0.911 to 0.950 g / cc, a Brookfield viscosity of 50,000 cP or less, and a molecular weight distribution (Mw,cc / Mn,cc) of 1.8 to 3.5; The bicomponent fibers have a shear viscosity ratio of the first composition to the second composition of less than 2.
0.
2. 2. The meltblown nonwoven fabric of claim 1, wherein the ethylene / alpha-olefin interpolymer has a Mz,cc / Mn,cc of less than 4.
0.
3. 3. The meltblown nonwoven fabric of claim 1 or 2, wherein the ethylene / alpha-olefin interpolymer has a weight fraction (w) of molecular weight greater than 105 g / mole, based on the total weight of the interpolymer, of less than 2.5%, as determined by conventional gel permeation chromatography.
4. The meltblown nonwoven fabric of any one of claims 1 to 3, wherein the ethylene / alpha-olefin interpolymer has a comonomer distribution breadth index greater than 50%.
5. The meltblown nonwoven fabric has a melt flow rate of 500 l / m at 20 gsm. 2 The meltblown nonwoven fabric according to any one of claims 1 to 4, exhibiting an air permeability of less than 1 / sec.
6. A composite structure comprising the meltblown nonwoven fabric of claims 1-5.
7. The composite structure of claim 6 , wherein the composite structure further comprises one or more spunbond nonwoven fabrics.
8. A composite structure having a SaMbSc configuration, where S is a spunbond nonwoven fabric, M is the meltblown nonwoven fabric of claims 1-5, and a, b, and c are the number of layers and are independent integers ranging from 1 to 5.
Citation Information
Patent Citations
Two-component fibers and fabrics made therefrom
JP2014532125A
Nonwoven fabric and method of forming same
JP2016528954A
Polymers for use in fibers and nonwovens, articles thereof, and composites thereof
JP2020512451A
Polymers for use in fibers and nonwoven fabrics, articles thereof, and composites thereof
WO2018169738A1